Penerapan Media Pembelajaran Inovatif Dalam Meningkatkan Minat Belajar Pendidikan Kewarganegaraan Siswa Kelas V SDN 1 Semarapura Kangin - fajriani, Anida; Dewa Bagus Sanjaya; Nengah Suastika (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2025)
This study aims to explore and analyze the application of innovative learning media in increasing the interest in learning Civic Education (PKn) of grade V students of SDN 1 Semarapura Kangin. The research method used is classroom action research (PTK) with a double cycle design. Data were collected through observation, interviews, and questionnaires. The results of the study indicate that the application of innovative learning media, such as interactive learning videos and educational games, can increase students' interest in learning Civics. This increase can be seen from the active participation of students in learning, better understanding of the material, and increased test scores. The implication of this study is the need to develop innovative learning strategies in increasing interest in learning Civics at SDN 1 Semarapura Kangin.